2021
DOI: 10.3389/fcimb.2021.750222
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Staphylococcus aureus Infection

Abstract: Staphylococcus aureus is an invasive, facultative intracellular pathogen that can colonize niches in various host organisms, making it difficult for the host immune system to completely eliminate. Host autophagy is an intracellular clearance pathway involved in degrading S. aureus. Whereas the accessory gene regulatory system of S. aureus that controls virulence factors could resist the host immune defenses by evading and even utilizing autophagy. This article reviews the interaction between autophagy and S. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…The intracellular survival mechanism of S. aureus contributes to pathogen dissemination among organ tissues, resulting in disease progression or recurrence (Löffler et al, 2014 ; Horn et al, 2018 ; Wang et al, 2021 ) and even being at a chronic situation. Plectasin, NZ2114, and MP1102 can kill intracellular S. aureus in human THP-1 macrophages and RAW 264.7 cells, respectively (Brinch et al, 2009 , 2010 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular survival mechanism of S. aureus contributes to pathogen dissemination among organ tissues, resulting in disease progression or recurrence (Löffler et al, 2014 ; Horn et al, 2018 ; Wang et al, 2021 ) and even being at a chronic situation. Plectasin, NZ2114, and MP1102 can kill intracellular S. aureus in human THP-1 macrophages and RAW 264.7 cells, respectively (Brinch et al, 2009 , 2010 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major causes of recurrent peritonitis is from the emergence of antibacterial resistance during antibiotic treatment, especially from methicillin-resistant and multiple resistant strains (Li et al, 2020a ; Camargo et al, 2021 ). In addition, S. aureus can invade and replicate in various host cells, complicating the usage of antibiotics (Zhou et al, 2018 ; Wang et al, 2021 ); therapeutic effects were impeded by poor penetration or inferior intracellular stability. Therefore, there is an urgent need to develop new intracellular antibacterial drugs with low resistance and high cellular permeability for the treatment or prevention of S. aureus -related peritonitis diseases.…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus is recruited to the autophagosome membrane by early phagosomes bearing Rab5 and Rab22b to LC3 labeled by Rab7 and LAMP-1 in the presence of Hla. S. aureus can inhibit the fusion of autophagosomes with lysosomes to form autolysosomes and thus replicate within the autophagosome without being killed [ 264 , 265 ]. However, S. aureus can inhibit autophagosome maturation and fusion with lysosomes, escape from autophagosomes into the cytoplasm, and lead to host cell death, which does not rely on caspase [ 266 ].…”
Section: Types Of Host Cell Death Caused By S Aureusmentioning
confidence: 99%
“…Consequently, it has been observed that genetic mutations affecting autophagic genes promote cellular degeneration [ 103 , 104 ], promote early-age-related phenotypes [ 105 , 106 ], tumor development [ 107 , 108 ], and susceptibility to infections in animals [ 109 , 110 ]. Similarly, mutations of genes related to autophagy are present in several Mendelian diseases in humans such as Rett’s syndrome, Parkinson’s disease, cataracts, several forms of cardiomyopathies, among others [ 111 ].…”
Section: Autophagy and Animal Healthmentioning
confidence: 99%